The evaluation of an interactive web-based Pulmonary Rehabilitation programme: protocol for the WEB SPACE for COPD feasibility study. Issue 8 (25th August 2015) - Chaplin, Emma; Hewitt, Stacey; Apps, Lindsay; Edwards, Kelly; Brough, Chris; Glab, Aga; Bankart, John; Jacobs, Ruth; Boyce, Sally; Williams, Johanna; Singh, Sally
Abstract : Introduction: Pulmonary Rehabilitation (PR) is an evidence-based intervention that has been recommended in guidelines to be available to those who may benefit. However, not all patients with chronic obstructive pulmonary disease (COPD) have access to this service. Healthcare services have shown the need for the provision of PR in other forms to enable patient choice and service capacity. There is an increase in evidence for the use of the internet in the management of long-term conditions to provide education and promote self-management. The aim of this study is to see if an interactive web-based PR programme is a feasible alternative compared with conventional PR. Methods and analysis: This is a feasibility study designed to evaluate the efficacy of providing a web-based PR programme to improve patients exercise capacity, quality of life and promote self-management in patients with moderate to severe COPD compared with conventional PR programmes. Eligible patients will be randomly allocated to receive either the web-based programme or conventional rehabilitation programme for 7 weeks using an internet-based randomisation system. Participants will be recruited from PR assessments, primary care and community rehabilitation programmes. Those randomised to the web-based programme work through the website which contains all the information that the patients receive in the PR classes. They receive weekly phone calls by a professional to help progress through the course on line. The outcome measures will be recruitment rates and eligibility as well as that standard for a PR assessment including measures of exercise capacity, quality of life questionnaires and physical activity. Ethics and dissemination: The research ethics committee for Northampton has provided ethical approval for the conduct of the study. The results of the study will be disseminated through appropriate conference presentations and peer reviewed journals. Trial registration number: ISRCTN03142263.